2013
DOI: 10.1038/ejhg.2013.161
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of cancer GWAS and candidate gene meta-analyses reveals limited overlap but similar effect sizes

Abstract: Candidate gene and genome-wide association studies (GWAS) represent two complementary approaches to uncovering genetic contributions to common diseases. We systematically reviewed the contributions of these approaches to our knowledge of genetic associations with cancer risk by analyzing the data in the Cancer Genome-wide Association and Meta Analyses database (Cancer GAMAdb). The database catalogs studies published since January 1, 2000, by study and cancer type. In all, we found that meta-analyses and pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 38 publications
2
41
0
2
Order By: Relevance
“…1 However, determining the precise biologic mechanism by which these loci lead to cancer susceptibility has proven challenging. More recently, there have been reports of specific germline haplotypes that increase the probability that a tumor acquires a specific mutation.…”
mentioning
confidence: 99%
“…1 However, determining the precise biologic mechanism by which these loci lead to cancer susceptibility has proven challenging. More recently, there have been reports of specific germline haplotypes that increase the probability that a tumor acquires a specific mutation.…”
mentioning
confidence: 99%
“…1,2 Multiple successful GWAS studies have been reported ranging from body size, metabolomics, and medically relevant traits (reviewed), 3,4 to hormones, 5 personality, 6 educational attainment, 7 and lifestyle characteristics. [8][9][10] The major technology behind these successes is the relatively cheap genotyping, in comparison with full genome sequencing, of DNA samples on genotyping arrays with 300 K-5 M single-nucleotide polymorphisms (SNPs), followed by imputation of the unmeasured SNPs.…”
Section: Introductionmentioning
confidence: 99%
“…The median imputation quality R 2 for MAF thresholds of 0.001, 0.01, 0.05, and 40.05 are 0.05, 0.28, 0.80, 0.99, respectively, for the 1000G imputed SNPs, with a similar quality for the autosomes and X chromosome, showing a good genome-wide coverage for association studies after imputation. 3,4 to hormones, 5 personality, 6 educational attainment, 7 and lifestyle characteristics. [8][9][10] The major technology behind these successes is the relatively cheap genotyping, in comparison with full genome sequencing, of DNA samples on genotyping arrays with 300 K-5 M single-nucleotide polymorphisms (SNPs), followed by imputation of the unmeasured SNPs.…”
mentioning
confidence: 99%
“…Therefore, among these candidate genes are those encoding proteins involved in androgen signaling, cell-cycle control mechanisms, major tumor-suppressors, or proto-oncogenes, as well as those involved in cellular adhesion or communication with surrounding cellular or matrix components of prostate epithelium [62,63]. This implies the need for previous knowledge when designing case-control studies using candidate gene approach [64].…”
Section: Candidate Gene-based Approachesmentioning
confidence: 99%